Fire design method for eccentrically loaded concrete‐filled steel tubular columns based on interaction diagrams. (13th September 2017) - Espinós, Ana; Albero, Vicente; Ibáñez, Carmen; Romero, Manuel L.; Hospitaler, Antonio
ABSTRACT: In this paper, a simplified design method for evaluating the fire resistance of eccentrically loaded concrete filled steel tubular (CFST) columns is presented. The developed method is based on the results of an extensive parametric analysis conducted in the framework of the RFCS European Project FRISCC (Fire resistance of innovative and slender concrete filled tubular composite columns) and is currently being evaluated by the Working Group SC4.T4 for its approval as the method to replace the current Annex H in EN1994‐1‐2, which was proved in previous investigations to be unsafe for slender columns. The method presented in this paper is based on the provisions of Clause 6.7.3.6 of EN 1994‐1‐1 for room temperature design, using bending moment – axial force interaction curves specially built up for the fire situation. These interaction curves are obtained by considering several possible positions of the plastic neutral axis within the cross‐section, and determining the internal forces and moments from the plastic stress blocks, which results particularly challenging for CFST sections subjected to elevated temperatures, given the thermal gradient that occurs within the cross‐section. For simplifying this process, equivalent temperatures are proposed, which allow using a single uniform temperature for representing each part of the composite section. Appropriate coefficients are also proposed for evaluating the effective flexural stiffness for second‐order analysis at elevated temperatures. The influence of the cross‐section shape, load eccentricity and percentage of reinforcement is accounted for in the proposal.